2022
DOI: 10.3389/fchem.2022.864663
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Dioxide Solubility in Nonionic Deep Eutectic Solvents Containing Phenolic Alcohols

Abstract: Deep eutectic solvents (DES) are a new class of green solvents that have shown unique properties in several process applications. This study evaluates nonionic DES containing phenolic alcohols as solvents for carbon dioxide (CO2) capture applications. Potential phenolic alcohols and the molar ratio between DES constituents were preselected for experimental investigations based on the conductor-like screening model for realistic solvation (COSMO-RS). CO2 solubility was experimentally determined in two different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 46 publications
(56 reference statements)
0
15
0
Order By: Relevance
“…It has also been reported that longer alkyl chain lengths of DESs, or hydrophobic moieties in general, are better solvents for CO 2 . 23,33 Bearing this in mind, novel DES combinations were chosen based on our ML predictions and the following DESs combinations are proposed at different molar ratios and a wide range of pressures: menthol–decanoic acid (1 : 2), menthol–dodecanoic acid (1 : 2), [TBP]Br-TEG, [TOA]Br-TEG, [TOMA]Br-TEG, [ATPP]Br-DECA, [ATPP]Br-EA, [ATPP]Br-MDEA, and [ATPP]Br-ECH. Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It has also been reported that longer alkyl chain lengths of DESs, or hydrophobic moieties in general, are better solvents for CO 2 . 23,33 Bearing this in mind, novel DES combinations were chosen based on our ML predictions and the following DESs combinations are proposed at different molar ratios and a wide range of pressures: menthol–decanoic acid (1 : 2), menthol–dodecanoic acid (1 : 2), [TBP]Br-TEG, [TOA]Br-TEG, [TOMA]Br-TEG, [ATPP]Br-DECA, [ATPP]Br-EA, [ATPP]Br-MDEA, and [ATPP]Br-ECH. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It has also been reported that longer alkyl chain lengths of DESs, or hydrophobic moieties in general, are better solvents for CO 2 . 23,33 Bearing this in mind, novel DES combinations were chosen based on our ML predictions and the following DESs combinations are proposed at different molar ratios and a wide range of pressures: mentholdecanoic acid (1 : 2), menthol-dodecanoic acid 12 shows the calculated solubility of CO 2 in the newly proposed DESs at 298.15 K and different pressures. As the pressure increases, the solubility of CO 2 predicted by the ML model also increases, in accord with Henry's Law.…”
Section: Green Chemistry Papermentioning
confidence: 99%
See 2 more Smart Citations
“…To overcome the main drawbacks of ionic DESs, particularly their toxicity and hygroscopicity, natural organic compounds have recently been suggested as constituents of hydrophobic nonionic eutectic systems [ 29 , 30 , 31 , 32 ]. Simple organic compounds have been used to prepare nonionic eutectic systems that were found to be superior to ionic DESs and ionic liquids in terms of viscosity, economy, and performance [ 33 , 34 ]. However, because most nonionic eutectic systems studied in the literature are nearly ideal mixtures, their eutectic temperature is not significantly lower than the melting temperatures of the pure constituents [ 6 , 35 ].…”
Section: Introductionmentioning
confidence: 99%